FluView and FluNet: Tools for Influenza Activity and Surveillance. Issue 4 (2nd October 2019) - Charbonneau, Deborah H.; James, LaTeesa N.
Abstract: Online resources can assist with locating and monitoring the spread of influenza. The aim of this review is to describe two online tools for tracking influenza activity: FluView from the Centers for Disease Control and Prevention in the United States and FluNet from the World Health Organization. Overall, these freely available online resources for influenza activity and surveillance may be helpful to a range of audiences including health providers, local governments, hospitals, schools, librarians, travelers, and members of the general public.